PEMAHAMAN SISWA TENTANG EQUAL SIGN DALAM MENYELESAIKAN TUGAS MATEMATIKA - Sartati, Setiawan Budi; Subanji, Subanji; Sisworo, Sisworo (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2018)
[Title: The Students' Understanding of Equal Sign in Completing Mathematics Tasks]. This study aims to describe the student's understanding of the equal sign to solve mathematical tasks. This study was included in the qualitative descriptive study. In this study, the data collected is the data of students work and verbal data (the interview). The subjects were six students of 7th class of MTs Attariqie Malang 2014/2015 (Junior High School), with details of two high-ability students, two students capable of being, and two low-ability students. Students' understanding of the equal sign examined further by providing tests and interviews in six research subjects. Interviews were conducted individually after the students work on the problems individually. The mathematical task load arithmetic and algebra problems. Based on the results of the study, all subjects were able to understand the equal sign as operational and the equal sign as a substitution. For equal sign as the basic relational, only high-ability students were able to understand it. Understanding of medium and low student capable entrenched in the operational pattern that is an equal sign as operational cause confusion to understanding equal sign as the basic relational, eg, 14+11=25+8 where students only pay attention to the results of operations that 14 plus 11 is 25 without notice relation of the addition of 8.